How Comte’s Sociological Perspective on Socio-Economic Transformations in Pondok Buntet Pesantren - Raza Syarif Hidayatullah; Syaripulloh Syaripulloh; Raka Dania Putra (International Journal Labs, 2025)
The socio-economic dynamics of Indonesian communities, especially in traditional institutions like Pondok Buntet Pesantren, are undergoing significant transformations due to the increasing integration of modern technologies and ideas. Pondok Buntet Pesantren, the oldest Islamic educational institution in Indonesia, plays a central role in shaping the local community's social and economic interactions. This research aims to analyze the socio-economic dynamics in Pondok Buntet Pesantren using Auguste Comte’s social evolution theory, which includes the theological, metaphysical, and positivist stages. The study uses qualitative methods with case study design, collecting data through interviews, observations, and document studies. The findings show that the community is transitioning from a religious value-based society to a more modern, technology-integrated one, with innovations such as QRIS being adopted in economic transactions. The Pesantren functions as an agent of social change, blending traditional values with modern technology and educational practices. This study contributes to understanding how Comte’s theory can be applied in socio-economic transformations, demonstrating how communities can integrate modernity without losing cultural identity. The research provides implications for developing community-based empowerment programs that promote economic transformation while preserving traditional values, although further studies with broader scope and quantitative methods are recommended.